2016
DOI: 10.21767/2573-5365.100018
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog in Nasal Mucus is a Biomarker for Smell Loss in Patients with Hyposmia

Abstract: Title: Sonic hedgehog in nasal mucus is a biomarker for smell loss in patients with hyposmia Background: Many chemical moieties have been identified in nasal and olfactory mucus related to cellular activity, cell signaling and olfaction. Sonic hedgehog (Shh) has been identified as a growth factor in taste buds but not in olfactory receptor tissues. We wished to determine if Shh were present in nasal mucus and, if present, does it relate to smell function and smell loss (hyposmia).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…These results are consistent with prior results of lowered nasal mucus Shh in patients with smell dysfunction . Based on the present results and those of other investigators, we hypothesize that Shh acts on stem or basal cells of taste buds to stimulate growth, development, and perpetuation of taste receptors and thereby activate and maintain taste function.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with prior results of lowered nasal mucus Shh in patients with smell dysfunction . Based on the present results and those of other investigators, we hypothesize that Shh acts on stem or basal cells of taste buds to stimulate growth, development, and perpetuation of taste receptors and thereby activate and maintain taste function.…”
Section: Discussionsupporting
confidence: 93%
“…The presence of Shh in human saliva is herein reported for the first time. Its presence in saliva and its lower concentration in patients with taste dysfunction compared to normals are consistent with data from our previous studies in which lower than normal levels of Shh were found in patients with smell dysfunction and from studies in which drugs which decreased Shh were associated with onset of taste dysfunction . The present results are also consistent with our hypothesis that Shh acts as a stimulator of taste receptor stem cells .…”
Section: Discussionsupporting
confidence: 92%
“…In fact, the presence of Shh in human saliva could function in maintaining normal homeostasis. Additionally, reports of Shh in nasal mucus and reduced levels in hyposmic patients suggest possible Hh pathway functions in olfaction [103].…”
Section: Chemosensation Somatosensation Hh Signaling and Disrupmentioning
confidence: 99%
“…Recent studies using animal models have revealed that the olfactory mucus contributes more directly to odorant detection. Proteins in the olfactory mucus contribute to several pre-receptor events such as enzymatic metabolism of odorants and recruiting odorants to receptor sites 8 13 . Despite the importance of the presumed functions of olfactory mucus, the molecular identities of the actors responsible for these functions remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%